Association of serum uric acid with albuminuria in type 2 diabetic patients with comorbid obesity and/or essential arterial hypertension - M. Marushchak; I. Krynytska; A. Lepyavko (Український Журнал Нефрології та Діалізу, 2022)
Abstract. Decompensation of diabetes mellitus type 2 (T2DM), duration of the disease, level of proteinuria, obesity and essential arterial hypertension (AH) play the main role in the development and progress of diabetic nephropathy.